2021
DOI: 10.21037/apm-21-191
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C level is associated with the recovery of renal function in cancer patients after onset of acute kidney injury

Abstract: Background: The risk of injury to the kidney can be significantly exacerbated by the presence of tumors and the effects of related treatments. Kidney injury associated with cancer is common in multiple myeloma, tumor lysis syndrome, hematopoietic stem cell therapy, and chemotherapy. Cancer patients are at increased risk of infection, sepsis, tumor lysis syndrome, drug-related toxicity, and other comorbidities, leading to a significantly increased risk of acute kidney injury (AKI). This study retrospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, for eGFRcys calculated based on cystatin C, 49 our results did not suggest a significant genetic causal role on kidney cancer, while the reverse MR analysis might indicate that kidney cancer was likely to decrease kidney function via the shared genetic mechanism with eGFRcys. This proved the fact that cystatin C might have the potential to play a role in identifying kidney function impairment for patients with kidney cancer 50 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, for eGFRcys calculated based on cystatin C, 49 our results did not suggest a significant genetic causal role on kidney cancer, while the reverse MR analysis might indicate that kidney cancer was likely to decrease kidney function via the shared genetic mechanism with eGFRcys. This proved the fact that cystatin C might have the potential to play a role in identifying kidney function impairment for patients with kidney cancer 50 …”
Section: Discussionmentioning
confidence: 92%
“…This proved the fact that cystatin C might the potential to play a role in identifying kidney function impairment for patients with kidney cancer. 50 In terms of the different performances of eGFRcys and eGFRcrea in detecting a causal link with kidney cancer, we would suggest there might be two main reasons. First, numerous previous clinical research studies indicated eG-FRcrea or eGFRcys could be applied to monitor patients but in different clinical situations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Malignant cancers were risk factors associated with poor prognosis of AKI patients as cancer patients were at increased risk of infection, sepsis, tumor lysis syndrome, drug-related toxicity, and other comorbidities. [ 26 , 27 ] SAPS-II and SOFA were important severity score systems for AKI patients in clinical practice, and higher SAPS-II or SOFA scores were associated with poor prognosis. [ 28 ] Herein, SAPS-II and SOFA scores were important variables associated with 30-day mortality of AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AKI defined by pRIFLE identifies some more patients with AKI (often refered to as R-AKI stages), than the KDIGO and AKIN systems, according to the compensative studies [30][31][32]. The categorization of severity of renal impairment we used the change in CysC-based GFR, because it has more accuracy and reliability comparing to GFR Creat in high risk population, confirmed by previous studies as well [33][34][35][36].…”
Section: In Our Studymentioning
confidence: 92%